Non-linear association of the metabolic score for insulin resistance with obstructive sleep apnea: a cross-sectional study from NHANES 2015–2018 - Cai, Zhimao; Li, Jiachen; Peng, Hui; Ye, Ye; Chen, Sixia; Zeng, Lingli; Lin, Jiashuang; Chen, Weifeng (Frontiers in Nutrition, 2025)
BackgroundThe relationship between the Metabolic Score for Insulin Resistance (METS-IR), a novel index integrating multiple metabolic parameters, and the risk of obstructive sleep apnea (OSA) remains under explored.MethodsAnalyses were conducted on data from 2,348 participants included in the National Health and Nutrition Examination Survey (NHANES) data from 2015 to 2018. Logistic regression, stratified analyses, curve-fitting analyses, and threshold effects analyses were employed to evaluate the association between METS-IR and the risk of OSA.ResultsMultifactorial logistic regression analyses revealed a significant positive correlation between METS-IR and the risk of OSA [OR: 1.05 (95% CI: 1.04–1.06)]. Stratified analyses showed consistent associations across various subgroups, including sex, race, age, marital status, education level, poverty income ratio, physical activity, alcohol use, smoking status, diabetes mellitus, hypertension, and cardiovascular disease. Nonlinear analysis identified an inflection point at METS-IR 46.65. On the left of the inflection point, the risk of OSA increased significantly, with each unit increase in METS-IR associated with a 7% increase in risk [OR: 1.07 (95% CI: 1.05–1.08)]. On the right side of the inflection point, however, the rate of risk increase slowed to 1% [OR: 1.01 (95% CI: 1.00–1.02)].ConclusionThis investigation reveals a significant and nonlinear relationship between METS-IR and OSA. Further investigation is needed to explore their association more comprehensively and to elucidate the underlying mechanisms.